Starting an iPhone application business for dummies - Nicholson, Aaron (--For dummies., 2010)
"IPhone apps are hot; the average app is downloaded more than 30,000 times. If you have some great apps in mind, Starting an iPhone Application Business For Dummies will show you how to produce and market them effectively. Starting an iPhone Application Business For Dummies provides clear, reliable business information to help developers and entrepreneurs create a profitable, sustainable business in this new and exciting market"--Resource description page